Μελέτη των αιωρούμενων σωματιδίων και χαρακτηρισμός τους, με σύστημα Lidar στην περιοχή Λεμεσού - Μακρομάλλη, Γεωργία (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Cyprus is considered to be rich in a variety of particulate matter due to its geographical position, so it is a point of study for this thesis. For this purpose, lidar measurements were made using the lidar system of the Cyprus University of Technology for day and evening recordings. After the Labview software has been processed, the levels of the atmospheric boundary layer and the levels of increased particle concentration have been identified, where they were designated accordingly. It is concluded that there are particles of local, remote areas and their mix, such as dust particles, human-origin suspensions from urban centers and industrial areas, biomass combustion smoke particles, and marine suspensions. More generally, the free troposphere of Cyprus shows increased concentrations of particulate matter and soil dust from Turkey, as well as urban fog. The cases for the period May-July 2017, where dust from the African continent appeared, were reduced.
Keywords: Atmosphere; Remote sensing; LIDAR; Aerosol optical properties; Ατμόσφαιρα; Τηλεπισκόπηση; Οπτικές ιδιότητες αερολυμάτων